Bioclimatic assessments for tea cultivation in Western Nghe An - Ngoc, Hoang Thi Huyen; Van, Tran Thi Thuy; Ha, Nguyen Manh; Binh, Nguyen Quoc; Tan, Mai Thanh (Vietnam Journal of Earth Sciences, 2019)
Bioclimatology is applied for growing tea in the West of Nghe An province, where the tea is considered as a high economic efficient plant to be priorly cultivated for reducing poverty and getting rich. Based on the bioclimatic characteristics of tea plant and regional climatic data from 1980 to 2014, the bioclimatic diagrams are built and the tea cultivability is mapped in term of annual average temperature and total precipitation, for this region with regarding its district of Con Cuong as an analytical key. The climate, including both temperature and precipitation, in Con Cuong is relatively suitable for the tea plantation. The Western Nghe An, a land of approx. 1.4 million ha, could be classified in five areas with different suitability for tea plant. The unfavorable area occupies only 1% of total region and the four favorable rests account for 99% of total, in which, the most favorable area is largest with about 746,355 ha, i.e. over 50% of whole region. The three other areas are cultivable but they are less favorable in terms of either temperature or precipitation. Growing tea in Western Nghe An, even in favorable areas, it should be taken into account of the weather disadvantages in certain moments of the year such as extreme dry, cold, hot and rainy events.ReferencesAhmed S., 2014. Tea and the taste of climate change, www.herbalgram.org, issue, 103, 44–51.Ahmed S., Stepp J.R., Orians C., Griffin T., Matyas C., 2014. Effects of extreme climate events on tea (Camellia sinensis) functional quality validate indigenous farmer knowledge and sensory preferences in tropical China. PloS one, 9(10), e109126.Bhagat R.M., Deb Baruah R., Safique S., 2010. climate and tea [camellia sinensis (l.) o. kuntze] Production with Special Reference to North Eastern India: A Review. Journal of Environmental Research And Development, 4(4), 1017–1028.Carr M., 1972. The Climatic Requirements of the Tea Plant: A Review. Experimental Agriculture, 8(01), 1–14. https://doi.org/10.1017/S0014479700023449.Carr M.K.V., Stephen W., 1992. Climate, weather and the yield of tea. In: Tea Cultivation to consumtpion. K.C. Wilson and  M.N. Clifford (Eds). Chapman and Hall, 87–135.Daleen Lotter, David le Maitre, 2014. Modeling the distribution of Aspalathus linearis (Rooibos tea): implications of climate change for livelihoods dependent on both cultivation and harvesting from the wild. Ecology and Evolution, 4(8), 1209–1221.Ducan J.M.A., Saikia S.D., Gupta N., Biggs E.M., 2016. Observing climate impacts on tea yield in Assam, India. Applied Geogr., 77, 64–71.Institute of Geography, 2016. Department of Climatically Geography. The precipitation and temperature data at meteorological measuring stations in the West of Nghe An Province between 1984 and 2014. Data stored at Department of Climatically Geography, Institute of Geography, Ha Noi, 46p.Gaussen H., 1954. 8 ème Congrès international de Botanique. Section 7 et 3. Paris.Hadfield W., 1976. The effect of high temperature on some aspects of the physiology and cultivation of tea bush (Camellia sinensis) in North East India. In: Light as an Ecological factor. G.C. Evans, R. Bainbridge and O. Rackham (Eds.) Blackwel Sci. Publ., London, 477–495.Hoang Luu Thu Thuy, 2012. The comprehensive assessment of natural, socio-economic and environmental conditions for environmental protection planning in Nghe An Province. Doctoral Thesis. Institude of Geography, Hanoi, 150p.Huang Shoubo, 1989. Meteorology of tea plants in China: a review. Agri. Forest Meteorol., 47, 19–30.Huang Shoubo, 1991. A study on the ecological climates of some famous tea growing areas in high mountainous regions of China. Chinese Geographical Science, 1(2), 121–128.International Center for Tropical Agriculture, 2017. Identification of suitable tea growing areas in Malawi under climate change scenarios. Ciat report, Cali, Colombia, 39p.Kabir S.E., 2001. A study on Ecophysiology of Tea (Camellia sinensis) with special reference to the influence of climatic factors on physiology of a few selected Tea clones of Darjeering. International Journal of Tea Science, 1(4), 1–9.Kandiah  S., Thevadasan T., 1980. Quantification of weather parameters to predict tea yields. Tea Q., Srilanka, 49(1), 25–33.Kaye L., 2014. Climate change threatens Sri Lanka’s tea industry. Triple Pundit: People, Planet, Profit. Available at: www.triplepundit.com/2014/06/climate-changethreatens-sri-lanka-tea-industry. Accessed July 25, 2014.Nakayama A., Harada S., 1962. Studies on the effect on the growth of tea plant. IV. The effect of temperature on the growth of young plants in summer. Bull. Tea Res. Station, Japan, 1, 28–40.Nguyen Bao Ve, 2005. The syllabus of industrial trees. Hanoi Argricultural Publishing House, 224p.Nguyen Dai Khanh, 2003. The assessment of agricultural climatic conditions for tea’s growth in major tea regions of Vietnam. Doctoral Thesis. Institute of Meteorology and Hydrology, 149p.Nguyen Khanh Van, Nguyen Thi Hien, Phan Ke Loc, Nguyen Tien Hiep, 2000. The bioclimatic diagrams of Vietnam. Vietnam National University Publishing House, Ha Noi, 126p.Nguyen Van Hong, 2017. Analyzing, assessing landscape for agriculture, forestry development and biodiversity conservation in the southwestern border districts in Nghe An province. Doctoral thesis. Vietnam National University, Hanoi, 150p.Nguyen Van Tao (ed.), 2004. Completing the asexual propagation process of LDP1 and LDP2 cultivars by cuttings in order to transfer to production. State Project of production pilot, coded KC.06.DA.09.NN. Institute of Tea Research, Phu Tho, 50p.Nkomwa E.C., Joshua M.K., Ngongondo C., Monjerezi M., Chipungu F., 2014. Assessing indigenous knowledge systems and climate change adaptation strategies in agriculture: A case study of Chagaka Village, Chikhwawa, Southern Malawi. Physics and Chemistry of the Earth, Parts A/B/C, 67–69, 164–172.Pham Hoang Ho, 2003. An Illustrated Flora of Vietnam, 2, 430–434. Youth Publishing House, 952p.Rebecca Boehm, Sean B. Cash, Bruce T. Anderson, Selena Ahmed, Timothy S. Grifﬁn, Albert Robbat Jr., John Richard Stepp, Wenyan Han, Matt Hazel and Colin M. Orians, 2016. Association between Empirically Estimated Monsoon Dynamics and Other Weather Factors and Historical Tea Yields in China: Results from a Yield Response Model. Climate, 4, 20; doi:10.3390/cli4020020. www.mdpi.com/journal/climate.Schepp K., 2014. Strategy to adapt to climate change for Michimikuru tea farmers in Kenya. Adap CC Report. 2008. Available at: www.adapcc.org/en/kenya.htm. Accessed July 25, 2014.Sen A.R., Biswas A.K., Sanyal D.K., 1966. The Influence of Climatic Factors on the Yield of Tea in the Assam Valley, J. App. Meteo., 5(6), 789–800.Statistics Office of Nghe An Province, 2016. The annual abstracts of statistics 2015. Nghe An Publishing House, Nghe An, 453p.Tanton T.W., 1982. Environmental factors affecting yield of tea (camellia sinensis). Effect of air temperature. Expl. Agri., 18, 47–52.The People’s Committee of Nghe An Province, 2013. The Decision No. 448/QĐ-UBND dated 31/01/2013 to approve the hi-tech agriculture planning on the production of tea in Nghe An Province.The People’s Committee of Nghe An Province, 2013. The Decision No. 6290/QĐ-UBND dated 24/12/2013 to approve the adjustments and supplements for the development of Nghe An tea Industrial zone planning in 2013–2020.Walter H, Lieth, 1967. Klimadiagram - Weltatlas. Veb Gustav Fischer Verlag Jena.Wijeratne M.A., 1996.  Vulnerability of Sri Lanka tea production to global climate change. Water, Air and Soil Pollution, 92(1-2), 87–94.Wijeratne M.A., Anandacoomaraswamy A., Amarathunga M., Ratnasiri J., 2007. Assessment of impact of climate change on productivity of tea (Camellia sinensis L.) plantations in Sri Lanka, 119–126.http://nghean.gov.vn, 05/06/2015. Many crops are withered in Con Cuong.http://baonghean.vn, 25/03/2013. Drought threaten rice and tea in Con Cuong. http://baonghean.vn/con-cuong-han-han-de-doa-lua-che-44581.html.